Salut As A Gate For The Coming Of Islam In Lombok: Archaeological Analysis Of The Ancient Mosque In North Lombok - Jamaludin Jamaludin (Center for Research and Development of Religious Literature and Heritage, 2018)
Salut is an old village that became the entrance of Islam in Lombok island. This is known from the historical evidence found in the village. Some of the ancient historical dwellings in Salut are ancient mosques with 17th century architectural styles and tombs of Islamic spreaders, which assert that Salut is the first region to accept Islam in Lombok Island. Based on the information from Babad Lombok, Salut is the first visited village by Islamic spreaders from Java through the Carik harbour. The existence of the ancient mosque and the old tomb as a historical relic is a proof of the success of Islam in North Lombok in the past. This article will discuss about the heritage of Islam as the initial evidence of the entry of Islam in Lombok. The entry evidences of Islam in Salut is in the form of archaeological heritage, so the approach used in this study is historical archaeological approach. Historical archeology tries to give the explanation of these remnants, using other social sciences as auxiliary science. There are three things to be studied in this article, first, reveal the archaeological remains of Islam in Salut Lombok Utara; second, reveal the growth and development of Islam in North Lombok and it’s relation with other areas in Lombok. Keywords: History, Islamization, Archeology, Ancient Mosque, Tombs.